Body Mass Index Changes in Children and Adolescents Treated with Methylphenidate for Attention Deficit Hyperactivity Disorder - Kousha , Maryam; Hasanpour Asli, Samaneh; Eslamdoust-Siahestalkhi, Fatemeh; Shoar, Yasmin; Shoar, Zohreh (Iranian Journal of Child Neurology, 2024)
Objectives Attention Deficit Hyperactivity Disorder (ADHD) and obesity are major pediatric public health problems. The present study aimed to examine the association between these two health parties in our pediatric populations. Materials & Methods This study is a single group retrospective cohort study about Body Mass Index (BMI) changes in 149 children and adolescents between 3-18 years old with a diagnosis of ADHD based on one child and adolescent psychiatrist interview according to the Diagnostic and Statistical Manual of Mental Disorders 4th edition criteria (DSMIV-TR). All participants were treated with methylphenidate. Besides, they were reassessed by the Kiddie Schedule for Affective Disorders and Schizophrenia-Present and Lifetime Persian version (K-SADS-PL-P). Furthermore, the height, weight, and BMI of participants were calculated. The data were analyzed by descriptive statistics, repeated measures, and Wilks’ lambda analysis using IBM SPSS Statistics version 23. Results The mean age of patients was 8.2±2.6 years, and 71.8% were boys. The obtained results showed that those treated with methylphenidate for more extended periods had higher BMI increases (p <0.001). The change in BMI was not related to the age at the start of treatment (p = 0.125), but this index was significantly different based on the years under treatment (p = 0.002). Moreover, changes in BMI were not significant based on gender (p = 0.850), the type of ADHD specifiers (p= 0.686), and concomitant drugs (p = 0.783).